The Effect of Credit Risk and Board Diversity on the Performance of Banks Listed on the Indonesian Stock Exchange - Suhardono, Adhyatma Ndaru; Simamora, Asnita; Agung, JR. Dwi Mas Sukma; Lestari, Henny Setyo; Leon, Farah Margaretha (IJIBE (International Journal of Islamic Business Ethics), 2023)
This research aims to analyze the influence of several factors on banking performance in Indonesia, with a focus on Return on Assets (ROA). The factors studied include the Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL) ratio, Expected Credit Loss Provision (CKPN) ratio, Earning Ability (BOPO), Loan to Deposit Ratio (LDR), and Board Diversity (BD). Data was taken from banking companies listed on the Indonesia Stock Exchange in the period 2018 to 2022. The analysis method uses a linear regression test with a Fixed Effect Model. The research results show that the NPL ratio, CKPN ratio, BOPO, LDR, and BD have a significant influence on banking performance, while CAR does not have a significant influence. These results provide important information for investors and managers in managing banks, as well as being the basis for further research in identifying other factors that influence banking performance in Indonesia.